2007
DOI: 10.1016/j.febslet.2007.05.081
|View full text |Cite
|
Sign up to set email alerts
|

ELOVL2 overexpression enhances triacylglycerol synthesis in 3T3‐L1 and F442A cells

Abstract: Elongation of very long-chain fatty acids (ELOVL) members were overexpressed in two preadipocyte cell lines, ELOVL2 and ELOVL3 in 3T3-L1 cells, and ELOVL1-3 in F442A cells. Cells overexpressing ELOVL2, whose preferred substrates are arachidonic acid (AA, C20:4nÀ6) and eicosapentaenoic acid (EPA, C20:5nÀ3), showed an enhanced triacylglycerol (TAG) synthesis and subsequent accumulation of lipid droplets. Incorporation of fatty acid (FA) but not of glucose into TAG was enhanced by ELOVL2-overexpression. Two lipog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 46 publications
(59 reference statements)
3
25
0
1
Order By: Relevance
“…However, as previous data from our laboratory showed that overexpression of Elovl2 in adipocytes promoted TG formation and lipid accumulation accompanied by an induction of PPARγ target genes (28), we analyzed hepatic expression of PPARγ and some of its target genes.…”
Section: Resultsmentioning
confidence: 99%
“…However, as previous data from our laboratory showed that overexpression of Elovl2 in adipocytes promoted TG formation and lipid accumulation accompanied by an induction of PPARγ target genes (28), we analyzed hepatic expression of PPARγ and some of its target genes.…”
Section: Resultsmentioning
confidence: 99%
“…The KCNJ15 gene encodes one of the potassium inward rectifying channels and is a type-2 diabetes risk gene and its up-regulation causes down regulation of glucose induced insulin release in mice and humans [33]. Similarly, the ELOVL2 gene (elongation of very long chain fatty acids 2) is located within 0.01 Mb upstream from SNP ASGA0030976 on SSC7 and is involved in enhancing the synthesis of triglycerides and deposition of lipid droplets in adipocytes [34]. The adipocytes usually produce leptin due to fat deposition [35].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, rs1150561 near ELOVL2 was associated with poorer L response. The product of this gene catalyzes the elongation of EPA to DHA (Kobayashi et al., 2007). Although our study suggests that ELOVL2 and FADS1 polymorphisms may also relate to L and MPOD response respectively, the mechanism of this relationship is uncertain, but it is probably connected to processes governing lipid composition in serum.…”
Section: Discussionmentioning
confidence: 99%